2023
DOI: 10.1108/ijieom-10-2022-0056
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of factors influencing patient length of stay in emergency departments

Abstract: PurposePatient length of stay (LOS) is an important indicator of emergency department (ED) performance. Investigating factors that influence LOS could thus improve healthcare delivery and patient safety. Previous studies have focused on patient-level factors to explain LOS variation, with little research into service-related factors. This study examined the association between LOS and multi-level factors including patient-, service- and organization-level factors.Design/methodology/approachThis study uses a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Factors such as TAT for diagnostics and specialty consultation, triage level and bed availability can significantly impact the average LOS. [12][13][14][15] Through root cause analysis (RCA), internal audits and observations, the current project identified similar factors affecting LOS, along with other reasons such as patient flow, personnel shortage, lack of equipment/diagnostic aids and decisions regarding patient discharge or transfer. The project team addressed these issues by implementing relevant strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as TAT for diagnostics and specialty consultation, triage level and bed availability can significantly impact the average LOS. [12][13][14][15] Through root cause analysis (RCA), internal audits and observations, the current project identified similar factors affecting LOS, along with other reasons such as patient flow, personnel shortage, lack of equipment/diagnostic aids and decisions regarding patient discharge or transfer. The project team addressed these issues by implementing relevant strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the Netherlands concluded that organizational factors, such as more consultations, testing in the ED and lower physician seniority were associated with longer ED LOS [7]. A variety of other studies revealed additional factors affecting ED LOS such as patient ethnicity, the timing of ED presentation, season of ED presentation, old age, insurance status, complexity of patient condition and ED physician treatment style [8,9].…”
Section: Introductionmentioning
confidence: 99%